1988
DOI: 10.1093/nar/16.14.6411
|View full text |Cite
|
Sign up to set email alerts
|

Replication of single-stranded DNA templates by primase-polymerase complexes of the yeast,Saccharomyces cerevisiae

Abstract: A partially purified primase-polymerase complex from the yeast, Saccharomyces cerevisiae, was capable of replicating a single stranded circular phage DNA into a replicative form with high efficiency. The primase-polymerase complex exhibited primase activity and polymerase activity on singly primed circular ssDNA as well as on gapped DNA. In addition, it was able to replicate an unprimed, single-stranded, circular phage DNA through a coupled primase-polymerase action. On Biogel A-O.5m filtration the primase-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The majority of studies have utilized partiallypurified enzymes and factors to reconstitute DNA synthetic activity [Fairman and Stillman, 1988;reviewed in Kelly, 1988;Stillman, 1989;Hurwitz et al, 1990;Tsurimoto et al, 1990]. Although some data exist on the functional association of several enzymes and factors [Mathews and Slabaugh, 1986;Vishwanatha et al, 1986;Tubo and Berezney, 1987;Biswas and Biswas, 1988;Syvä oja and Linn, 1989;Reddy and Fager, 1993;Maga and Hü bscher, 1996], the precise molecular interactions that occur between the proteins required to support DNA replication remain largely undefined. The ability to reconstitute DNA replication activity utilizing individual components does not exclude the existence of large multiprotein complexes containing many or all of the proteins that function in vivo to replicate DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies have utilized partiallypurified enzymes and factors to reconstitute DNA synthetic activity [Fairman and Stillman, 1988;reviewed in Kelly, 1988;Stillman, 1989;Hurwitz et al, 1990;Tsurimoto et al, 1990]. Although some data exist on the functional association of several enzymes and factors [Mathews and Slabaugh, 1986;Vishwanatha et al, 1986;Tubo and Berezney, 1987;Biswas and Biswas, 1988;Syvä oja and Linn, 1989;Reddy and Fager, 1993;Maga and Hü bscher, 1996], the precise molecular interactions that occur between the proteins required to support DNA replication remain largely undefined. The ability to reconstitute DNA replication activity utilizing individual components does not exclude the existence of large multiprotein complexes containing many or all of the proteins that function in vivo to replicate DNA.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins include DNA polymerases a and d, DNA topoisomerases I and II, DNA primase, DNA ligase I, proliferating cell nuclear antigen (PCNA), replication factor C (RFC), replication protein A (RPA), and the nucleases RNase H1 and FEN1/RTH1 [reviewed in Stillman, 1994;Hickey and Malkas, 1997;Malkas, 1998]. Increasing evidence has supported the concept that many of the enzymes and factors involved in the replication of mammalian DNA function together as an organized multiprotein complex [Baril et al, 1983;Jackson and Cook, 1986;Mathews and Slabaugh, 1986;Vishwanatha et al, 1986;Tubo and Berezney, 1987;Biswas and Biswas, 1988;Syvä oja and Linn, 1989;Reddy and Fager, 1993;Maga and Hü bscher, 1996;Hickey and Malkas, 1997;Malkas, 1998]. We have previously reported that a DNA replication-competent multiprotein form of DNA polymerase can be isolated from a variety of mammalian cell lines and tissues [Malkas et al, 1990;Wu et al, 1994;Applegren et al, 1995;Coll et al, 1996Coll et al, , 1997Tom et al, 1996;Lin et al, 1997].…”
mentioning
confidence: 99%
“…M13-ARS, containing an 837-base-pair (bp) HindIII-EcoRI fragment of ARS1, was subcloned in M13SK phagemid (Stratagene, La Jolla, Calif.) as previously described (3). Construction of TF1-ARS and TF5-ARS plasmids was as previously described (10,11).…”
Section: Cm)mentioning
confidence: 99%
“…We identified earlier a high molecular weight form of primase-polymerase complex from Saccharomyces cerevisiae which was capable of rapid and processive DNA synthesis on an unprimed single-stranded DNA template (Biswas & Biswas, 1988). In this paper, we describe the purification of a multimeric form of DNA polymerase a to homogeneity.…”
mentioning
confidence: 99%
“…These four subunits may likely be a part of a larger multiprotein complex that represents the replicating form of polymerase a. In fact, studies in several laboratories have indicated that DNA polymerase a could be isolated as a large complex accompanied by a number of enzymatic activities such as polymerase, primase, and exonuclease (Hubscher et al, 1982;Baril et al, 1983; Takada et al, 1986;; Biswas & Biswas, 1988). The multimeric form of t This work was supported by a grant from the U.S. Public Health Service.…”
mentioning
confidence: 99%